Competitive Beauty Salon Strategies: Professional Knowledge, Management Competencies, Relationship Skills, and Practical Experience - Anatasia, Velly; Widhianto, Chandra Wibowo; Gularso, Kurnadi; Welhenly, Veronica Cynthia (Universitas Bunda Mulia, 2026)
This study investigates how professional knowledge, operational management skills, strategic insight, relationship-building competence, and practical experience influence the competitive strength of beauty salons. Competitiveness was evaluated based on customer perceptions. A quantitative methodology was adopted, using questionnaires to collect data from 110 beauty salon owners or managers in the Jakarta region. The collected data were then analyzed through Structural Equation Modeling, employing the Partial Least Squares method (SmartPLS 4). The findings indicate that professional knowledge has a significant positive impact on competitiveness compared to other businesses, and its influence is crucial for shaping customer perspectives. However, operational management competencies did not demonstrate a substantial impact on enhancing the company's competitiveness. Conversely, relationship skills competencies and practical experience significantly and positively influence competitiveness, with practical experience emerging as the strongest factor. Further studies are suggested to reconsider the use of operational management competencies as a variable or replace them with more relevant factors that directly shape customer perceptions and enhance efficiency to build a strong salon competitiveness. Furthermore, an emphasis on strategies focused on differentiation and agility of service providers in salons is crucial in responding to competition in the market share of beauty service providers, especially salons.